Assessment of soil fertility and water dynamics under different tillage practices in loess degraded soil of Balochistan (Journal of Agriculture and Veterinary Science, 2024)
The soils of Pakistan, particularly in Balochistan, face numerous challenges including low organic matter content and instability exacerbated by high temperatures and alkalinity. This degradation has led to stagnation and diminished agricultural productivity and soil fertility. Balochistan, in particular, grapples with severe water and nutrient deficiencies, with much of its highlands relying solely on groundwater for irrigation and drinking purposes. Effective water management and soil moisture conservation practices are essential in water-scarce arid and semi-arid regions. Adopting appropriate tillage systems can help mitigate the adverse effects of water scarcity. In this study, conducted from 2020 to 2021 at Balochistan Agriculture University, Quetta, we aimed to assess water dynamics and nutrient concentrations under different tillage practices in the uplands of Balochistan. Specifically, our objectives were to measure water content in wheat fields and evaluate nutrient concentrations under various management practices. Treatments included conventional tillage (CT), zero tillage (ZT), and chisel plough (CP), replicated thrice in a Randomized Complete Block Design (RCBD). Parameters measured under different treatments included soil pH, electrical conductivity (EC), soil temperature, soil water content (SWC), organic matter (OM), available phosphorus (P), nitrate nitrogen (N), extractable potassium (K), as well as crop data such as biological yield (kg/ha) and grain yield (kg/ha). Statistical analysis, utilizing analysis of variance (ANOVA), revealed non-significant differences among the parameters studied. However, we recommend further research and continued investigation into tillage systems for sustainable agricultural practices in Balochistan.